A Retrospective Study of Missed Fractures and Injuries in Orthopedics - Sapkota, Krishna; Ranjeet, Niraj (Nepal Journal of Medical Sciences, 2023)
Introduction: Common Orthopedics injuries may result in long-term disability when they are treated lately. Simple fractures may require surgeries when they are missed and neglected. Most musculoskeletal injuries are seen in emergencies, some injuries may be missed when life-threatening conditions require attention, especially in poly-trauma patients. Certain injuries are difficult to recognize and some fractures may not visible in initial x-rays. A high index of suspicion is required to diagnose such cases. Methods: We conduct a retrospective study in which missed fractures, dislocations, and injuries were diagnosed and noted by consultant Orthopaedic surgeons from 2013 to 2022. Results: There were 76 missed diagnosed cases noted from 2013 to 2022. The patient’s ages range from 2 years to 63 years. Altogether 42(55.3%) were missed fractures, 23 (30.3%) were missed dislocations, and 11(14.5%) were tendon and ligament injuries cases. The common reason for the error was related to radiological error found in 62 (81.6%) cases. Misreading of X-rays was seen in 22 (28.9%) cases, poor quality x-rays in 17 (22.4%) cases, improper x- rays in 10 (13.2%) cases, and failure to order for x-rays in 16 (21.1%) cases. Conclusions: Good history and clinical examinations are essential. Proper x-rays should be taken and poor-quality x- rays should not be accepted but repeated. Most injuries missed on radiographs are not difficult to diagnose. Re-evaluation of patients should be done in an emergency, and with poly-trauma patients.